Social Media: An Online Veritable Link for Studentsâ€™ Employability Skills (A Case of Osun State Technical Colleges, Nigeria) - Olowo, Busuyi Francis; Akinguloye, Babatunde Akinwande; Gambo, Omobola Oyinlade; Jembola, Olujoke Emily (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2020)
Social media is an indispensable tool for students to develop and improve their employability skills. This paper reported a survey that investigated the use of Social media (LinkedIn, Youtube, WhatsApp, Facebook, and Twitter) and its influence on studentsâ€™ employability skills in Osun State Technical Colleges. The study adopted quantitative approach of design. The population of the study comprised all 3,029 students of Osun State technical colleges. The sample of 354 students was randomly selected. An instrument titled â€œUse of Social Media Platform and Studentsâ€™ Employability Skills Questionnaire (SMSESPQ)â€ was used.Â Data were analysed using multiple regression statistics at .05 level of significant. The findings showed that the use of Youtube (Î²= .611, P0.05), LinkedIn (Î²= .571, P0.05), Facebook (Î²= .487, P0.05), WhatsApp (Î²= .452, P0.05), and Twitter (Î²= .343, P0.05) were found to be significantly contributed to studentsâ€™ employability skills in Osun State Technical Colleges. The study concluded that that the use of Youtube, LinkedIn, Facebook, WhatsApp, and Twitter enhanced and contributed to studentsâ€™ employability skills in Osun State Technical Colleges. The study implicated that students in Osun State Technical Colleges and other Technical Colleges in Nigeria should admire the use of social medial such as Youtube, LinkedIn, Facebook, WhatsApp, and Twitter purposely to have access to information, videos, and pictures that will train and improve them to be able to plan, arrange, coordinate, communicate, corporate and execute projects toward achievement of goals.